Pengaruh Terapi Kompres Hangat Terhadap Intensitas Nyeri Pada Bayi Saat Imunisasi - Maskaum Hasibuan; Tetti Seriati Situmorang; Ernamari Ernamari (Jurnal Kebidanan, 2023)
According to WHO in 2017, an estimated 19.9 million babies worldwide did not reach basic immunization services such as 3 doses of the DPT vaccine. About 60% of these babies live in 10 countries including Indonesia. Pain due to immunization is a condition of discomfort that can be a barrier to immunization. In addition, the pain that occurs during immunization makes parents disobedient to their child's immunization schedule. This research is a quasi-experimental study with a post test only control group design approach. The purpose of this study was to analyze the effect of warm compress therapy on pain intensity in infants during immunization. The population in this study were all infants aged 0-12 who came to the posyandu for basic immunization in June 2022 in the Working Area of the Datuk Bandar Health Center, Tanjung Balai City, 2022. Sampling used a non-probability sampling technique with a consecutive sampling approach. The number of samples was 40 infants (divided into 2 experimental and control groups each of 20). Data analysis using the Mann-Whitney test. The test results obtained p = 0.000 0.05. There is a significant effect of warm compress therapy on the intensity of pain in infants at the Datuk Bandar Health Center in 2022. It is recommended that the UPT Datuk Bandar Health Center recommend warm compresses at the injection injection site, in order to reduce the pain response.  Keywords: Warm compresses, pain intensity, immunization, babies